Comparative Effectiveness Research: Alternatives to "Traditional" Computed Tomography Use in the Acute Care Setting. (17th November 2015) - Moore, Christopher L.; Broder, Joshua; Gunn, Martin L.; Bhargavan‐Chatfield, Mythreyi; Cody, Dianna; Cullison, Kevin; Daniels, Brock; Gans, Bradley; Kennedy Hall, M.; Gaines, Barbara A.; Goldman, Sarah; Heil, John; et al.
Abstract: Computed tomography (CT) scanning is an essential diagnostic tool and has revolutionized care of patients in the acute care setting. However, there is widespread agreement that overutilization of CT, where benefits do not exceed possible costs or harms, is occurring. The goal was to seek consensus in identifying and prioritizing research questions and themes that involve the comparative effectiveness of "traditional" CT use versus alternative diagnostic strategies in the acute care setting. A modified Delphi technique was used that included input from emergency physicians, emergency radiologists, medical physicists, and an industry expert to achieve this.